2009
DOI: 10.4255/mcpharmacol.09.06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiation-induced TGF-beta Signaling in Cancer Therapy

Abstract: TGF-β signaling regulates several different biological processes involving cell-growth, differentiation, apoptosis, motility, angiogenesis, epithelial mesenchymal transition and extracellular matrix production that affects embryonic development and pathogenesis of various diseases, including cancer, its effects depending on the cellular context and physiological environment. Growth suppression mediated by TGF-β signaling often associated with inhibition of c-myc, cdks and induction of p15, p27, Bax and p21. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 94 publications
5
83
0
1
Order By: Relevance
“…94 In early stages TGFb may play a role in suppression of malignancy but at later stages may promote tumor progression. 95,96 Since TGFb induces tenascin-C expression, 97 it is intriguing to speculate that this pathway may contribute to tenascin-C induction by radiotherapy. In addition, irradiation induced hypoxia or inflammation might also trigger tenascin-C expression by other pathways.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…94 In early stages TGFb may play a role in suppression of malignancy but at later stages may promote tumor progression. 95,96 Since TGFb induces tenascin-C expression, 97 it is intriguing to speculate that this pathway may contribute to tenascin-C induction by radiotherapy. In addition, irradiation induced hypoxia or inflammation might also trigger tenascin-C expression by other pathways.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…Low-dose radiation (50 mGy gamma-rays) exposure of normal cells showed some bystander effects on transformed cells leading to their apoptosis in a TGF-beta-dependent manner. 22 Although TGF-beta typically represses NF-kappaB signaling in normal cells, recent in vitro and in vivo evidence suggests an aberrant ability of TGF-beta signaling to activate NF-kappaB signaling in several different cancers as a means of promoting malignant tumor cell phenotypes. 32,33 Aspirin was also shown to have such a dual nature in NF-kappaB regulation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another study revealed that the TGF-beta overexpression after the radiation exposure induced TGF-beta signaling through the induction of Smad7 and TGF-beta type II receptor. 22 It is also involved in the activation of p53 and ataxia telangiectasia mutated (ATM) signaling pathways thereby increasing apoptosis in irradiated cells. Low-dose radiation (50 mGy gamma-rays) exposure of normal cells showed some bystander effects on transformed cells leading to their apoptosis in a TGF-beta-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Имеющиеся данные свидетельствуют о том, что активация TGF-β1-пути является одной из основных причин неблагоприятно-го прогноза [9]. Показано, что у больных РЛ повыше-ны уровни TGF-β1 в плазме крови как исходные, так и после лучевой терапии [10].…”
Section: Introductionunclassified